Chronic Inflammation and Cancer: The Role of Endothelial Dysfunction and Vascular Inflammation - Malhab, Lara J. Bou; Saber-Ayad, Maha M.; Al-Hakm, Ranyah; Nair, Vidhya A.; Paliogiannis, Panagiotis; Pintus, Gianfranco; Abdel-Rahman, Wael M. (Current Pharmaceutical Design, 2021)
Long-lasting subclinical inflammation is associated with a wide range of human diseases, particularly at a middle and older age. Recent reports showed that there is a direct causal link between inflammation and cancer development, as several cancers were found to be associated with chronic inflammatory conditions. In patients with cancer, healthy endothelial cells regulate vascular homeostasis, and it is believed that they can limit tumor growth, invasiveness, and metastasis. Conversely, dysfunctional endothelial cells that have been exposed to the inflammatory tumor microenvironment can support cancer progression and metastasis. Dysfunctional endothelial cells can exert these effects via diverse mechanisms, including dysregulated adhesion, permeability, and activation of NF-ΚB and STAT3 signaling. In this review, we highlight the role of vascular inflammation in predisposition to cancer within the context of two common disease risk factors: obesity and smoking. In addition, we discuss the molecular triggers, pathophysiological mechanisms, and the biological consequences of vascular inflammation during cancer development and metastasis. Finally, we summarize the current therapies and pharmacological agents that target vascular inflammation and endothelial dysfunction.
Keywords: smoking